The relationship between the theory of social representations and the importance of their study in university teachers - Arias-Holguín, Martha Lucía; Moya-Espinosa, Pedro Ignacio (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The theory of social representations has been studied to analyze diverse and varied problems, however, little research based on this theory from the field of study of the university teacher has been addressed. The aim of this reflection is to establish the relationship between the professor and the importance of mentioning their social representations, constituting a contribution to support its analysis and research. It is conceptualized from different authors about the meaning of Social Representations and the importance of their study to analyze the work of university teachers, subject agent of change for the educational quality of the university. We conclude that higher education should enable the knowledge of Social Representations, circulating in the educational context by analyzing their impact on individual and group behavior, allowing the understanding of the work of educational actors, their impact and intervention in processes leading to a better education.